On Epimorphically Closed Homotypical Permutative Varieties - Khan, Noor Mohammad (Kathmandu University Journal of Science, Engineering and Technology, 2007)
We find some sufficient conditions that a homotypical identity be preserved under epis of semigroups in conjunction with any nontrivial permutation identity.